The relationship between smoking intensity and subclinical cardiovascular injury: The Multi-Ethnic Study of Atherosclerosis (MESA). (March 2017) - Al Rifai, Mahmoud; DeFilippis, Andrew P.; McEvoy, John W.; Hall, Michael E.; Acien, Ana Navas; Jones, Miranda R.; Keith, Rachel; Magid, Hoda S.; Rodriguez, Carlos J.; Barr, Graham R.; Benjamin, Emelia J.; Robertson, Rose Marie; et al.
Abstract: Background and aims: Modern tobacco regulatory science requires an understanding of which biomarkers of cardiovascular injury are most sensitive to cigarette smoking exposure. Methods: We studied self-reported current smokers from the Multi-Ethnic Study of Atherosclerosis. Smoking intensity was defined by number of cigarettes/day and urinary cotinine levels. Subclinical cardiovascular injury was assessed using markers of inflammation [high-sensitivity C-reactive protein (hsCRP), interleukin 6 & 2 (IL-2 & IL-6), tumor necrosis factor alpha (TNF-α)], thrombosis (fibrinogen, D-dimer, homocysteine), myocardial injury (troponin T; TnT), endothelial damage (albumin: creatinine ratio), and vascular function [aortic & carotid distensibility, flow-mediated dilation (FMD)]. Biomarkers were modeled as absolute and percent change using multivariable-adjusted linear regression models adjusted for cardiovascular risk factors and smoking duration. Results: Among 843 current smokers, mean age was 58 (9) years, 53% were men, 39% were African American, mean number of cigarettes per day was 13 (10), and median smoking duration was 39 (15) years. Cigarette count was significantly associated with higher hsCRP, IL-6 and fibrinogen (β coefficients: 0.013, 0.011, 0.60 respectively), while ln-transformed cotinine was associated with the same biomarkers (β coefficients: 0.12, 0.04, 5.3 respectively) and inversely associated with aortic distensibility (β coefficient: −0.13). There was a limited association between smoking intensity and homocysteine, D-dimer, and albumin:creatinine ratio in partially adjusted models only, while there was no association with IL-2, TNF-α, carotid distensibility, FMD, or TnT in any model. In percent change analyses, relationships were strongest with hsCRP. Conclusions: Smoking intensity was associated with early biomarkers of CVD, particularly, markers of systemic inflammation. Of these, hsCRP may be the most sensitive. Highlights: Smoking intensity was associated with hsCRP, IL-6, fibrinogen, and aortic distensibility. hsCRP was the most sensitive biomarker of tobacco-related cardiovascular injury of 12 biomarkers tested in this study. hsCRP may help in the study of potential cardiovascular effects of novel tobacco products.